Prevalence of Lebanese stroke survivors: A comparative pilot study - Nathalie Lahoud; Pascale Salameh; Nadine Saleh; Hassan Hosseini (Springer, 2019)
Stroke is a leading cause of morbidity and mortality worldwide and its late burden has mainly been attributable to developing countries. Lebanon is one of these countries where epidemiological studies on stroke burden are scarce but necessary. Thus, the present study was conducted to assess the prevalence of stroke survivors among Lebanese inhabitants. A cross-sectional survey was carried out using randomly selected landline phone numbers on all governorates to retrieve data on stroke survivors and their sociodemographic characteristics. Results were then standardized over the Lebanese and the World Health Organization (WHO) world populations. A total of 6963 Lebanese inhabitants were included in the study; among these were 56 stroke survivors. This led to an adjusted stroke prevalence of 0.50% [95% confidence interval (CI) = 0.33-0.66%] and a world-standardized prevalence of 0.60% (95% CI = 0.42-0.78%). A significantly higher stroke prevalence was found among older age groups and more socioeconomically privileged areas. Overall, the study showed a relatively higher prevalence of stroke in this sample of Lebanese inhabitants when compared to other developing countries. However, larger community-based studies with a clinical assessment of stroke cases are needed to confirm our findings.